Hello Everyone,

I have searched the forums and can't seem to find an answer which satisfies my question. I hope this dosen't irritate anyone as it is a very basic question.

I have been fiddling around with some bodmas questions and have hit a brick wall, I can get the correct answer however the final bit of the process is confusing me and I want to understand it rather than "just know it works".

Below is my problem.

12 + 9 - 18 + 4 -15 + 6 -8

= (12+9) + (4+6) -

(18 - 15) - 8

<===This should be (12+9)+(4+6)-(18+15)-8. Remember, the 18 and 15 are both negative, so when you group them you must precede the group with a negative sign and change both their signs within the group.
= (21+10) - (18+15)

+ 8 < This is the part I am confused about

Should be -8
= 31 - 41 = -10

Why does it change from (18-15) - 8 to (18+15) + 8. It must have something to do with their being two minus but I thought the two negatives make a positive rule only worked with negative numbers.

Thanks in advance.